New Perspectives for the Development of Track-Bound Traffic - Hugenberg, Gerd (Promet - Traffic&Transportation, 2012)
A brief hommage is rendered to Hermann Kemper (1892--1977), the inventor oft he magnetic levitation tecnique for highspeed transport